Laser surface modification of alloys for corrosion and erosion resistance - Kwok, Chi Tat. (Cambridge, UK ; Philadelphia, PA : Woodhead Publishing, 2012)
Corrosion and erosion processes often occur synergistically to cause serious damage to metal alloys. Laser surface modification techniques such as laser surface melting or alloying are being increasingly used to treat surfaces to prevent corrosion or repair corroded or damaged components. Laser surface modification of alloys for corrosion and erosion resistance reviews the wealth of recent research on these important techniques and their applications. After an introductory overview, part one reviews the use of laser surface melting and other techniques to improve the corrosion resistance of stainless and other steels as well as nickel-titanium and a range of other alloys. Part two covers the use of laser surface modification to prevent different types of erosion, including liquid impingement, slurry (solid particle) and electrical erosion as well as laser remanufacturing of damaged components. With its distinguished editor and international team of contributors, Laser surface modification of alloys for corrosion and erosion resistance is a standard reference for all those concerned with preventing corrosion and erosion damage in metallic components in sectors as diverse as energy production and electrical engineering. Reviews recent research on the use of laser surface modification techniques, including the prevention of corrosion and repair of corroded or damaged componentsDiscusses the techniques for improving the corrosion resistance of steels, nickel-titanium and a range of alloysAnalyses the use of laser surface modification to prevent different types of erosion, including liquid impingement and laser remanufacturing of damaged components.
Part 1 Improving corrosion and cracking resistance: Laser surface modification of steel and cast iron for corrosion resistance -- Laser surface melting (LSM) to repair stress corrosion cracking (SCC) in weld metal -- Laser surface melting (LSM) of stainless steels for mitigating intergranular corrosion (IGC) -- Pulsed laser surface treatment of multilayer gold nickel copper (Au/Ni/Cu) coatings to improve the corrosion resistance of components in electronics -- Laser surface modification of nickel titanium (NiTi) alloy biomaterials to improve biocompatibility and corrosion resistance. Part 2 Improving erosion corrosion resistance: Laser surface modification of metals for liquid impingement erosion resistance -- Laser surface modification of steel for slurry erosion resistance in power plants -- Laser surface alloying (LSA) of copper for electrical erosion resistance -- Laser remanufacturing to improve the erosion and corrosion resistance of metal components -- Laser surface remelting to improve the erosion corrosion resistance of nickel chromium aluminium yttrium (NiCrAlY) plasma spray coatings.
Includes bibliographical references and index.
Keywords: Corrosion resistant alloys; Surface hardening; SCIENCE -- Chemistry -- Industrial & Technical; TECHNOLOGY & ENGINEERING -- Chemical & Biochemical; Corrosion resistant alloys; Surface hardening